Juvenile territorial constructions and their psychosocial aspects in perspective of the Urban renewal macroproject, Comuna San José, Manizales, Colombia - Jurado-Alvarán, Claudia; Ocampo-Castaño, Ricardo Alberto (Prospectiva. Revista de Trabajo Social e Intervención Social, 2018)
This article reveals the results of a study that analyses the psychosocial impact produced by the transformations of territory generated by a project of urban renovation in the district of San José in the city of Manizales.The interactive study was conducted with constant collaboration of the youth in the district. A permanent dialogue was established between the social actors and the researchers who were interested in  the reality of the youth from their point of view.It was found that the transformation of territory forms new meanings of life, family and neighbourhood, and highlights fractures in the construct of identity and the uprooting of generational and community legacy of youth. Equally, such transformation causes alterations in the youth’s psychosocial condition, and these are reflected in tendency towards depression, weakening of the sense of community and changes in their personal, family and community identity. Finally, the transformation also causes socio-economic deterioration which generates insecurity in the neighbourhood, an increase in drug addiction and the loss of recreational zones.